Development of E-Modules Based on Scientific Approach for Respiratory System Material for Class VIII at MTsN Gowa - Laisa, Bau' Febrianti; Rivai, Andi Tenri Ola; Syahriani, Syahriani (JURNAL BIOEDUKASI, 2025)
The Independent Curriculum emphasizes the importance of active student participation in the learning process. Therefore, teaching materials are needed that can encourage student interest and motivation to learn. One alternative that can be developed is an e-module, because it can support independent learning while supporting a more interactive learning process. The e-module used needs to be developed with an approach so that students are more active in constructing their knowledge and skills. An approach that can encourage students to investigate and discover facts from everyday events is a scientific approach. One of the materials that is less understood by students in class is the respiratory system. This study aims to produce an e-module based on a scientific approach for the respiratory system material for grade VIII at MTsN Gowa that can help and facilitate students in learning science lessons. The research method used is Research and Development (R&D). This study uses the ADDIE development model with stages, namely 1) Analysis 2) Design 3) Development 4) Implementation 5) Evaluation. The research instruments used were instrument validation sheets, teaching modules, student and educator response questionnaires, and learning outcome test instruments. Data analysis consisted of validity, practicality, and effectiveness analysis. The results of the study showed that the validity of producing e-modules based on a scientific approach to the respiratory system material developed was in the very valid category (3.7) and the practicality of producing e-modules based on a scientific approach to the respiratory system material developed was in the practical category (3.4) and was effective because 93% of students obtained a passing grade.